Big data in psychological research - Woo, Sang Eun; Tay, Louis (Psychologist); Proctor, Robert W. (Washington : American Psychological Association, 2020)
"Technological advances have led to an abundance of widely available data on every aspect of life today. Psychologists today have more information than ever before on human cognition, emotion, attitudes, and behavior. Big Data in Psychological Research addresses the opportunities and challenges that this data presents to psychological researchers. This edited collection provides an overview of theoretical approaches to the utility and purpose of big data, approaches to research design and analysis, collection methods, applications, limitations, best practice recommendations, and key issues related to privacy, security, and ethical concerns that are essential to understand for anyone working with big data. The book also discusses potential future research directions aimed at improving the quality and interpretation of big data projects, as well as the training and evaluation of psychological science teams that conduct research using big data"--
Sadrži bibliografiju i kazalo.
Keywords: Psychology -- Research -- Data processing; Psychology -- Research -- Methodology